Adaptation of Staphylococcus aureus to Airway Environments in Patients With Cystic Fibrosis by Upregulation of Superoxide Dismutase M and Iron-Scavenging Proteins. (6th January 2018) - Treffon, Janina; Block, Desiree; Moche, Martin; Reiss, Swantje; Fuchs, Stephan; Engelmann, Susanne; Becher, Dörte; Langhanki, Lars; Mellmann, Alexander; Peters, Georg; Kahl, Barbara C
Abstract: Adaptation of S. aureus to the hostile environment of CF airways resulted in changed abundance of proteins involved in energy metabolism, cellular processes, transport and binding, but most importantly in an iron-scavenging phenotype and increased activity of superoxide dismutase M. Abstract : We explore the drivers of the spatiotemporal distribution of the highly lethal Nipah virus and demonstrate that year-to-year variability in the number of spillovers is linked to annual temperature differences and that spatial variability is associated with the distance to surveillance hospitals.